دراسة في الإطار الجغرافي والتاريخي لإقليم التيطري A Study In The Geographical And Historical Framework Of The Province Of Titeri - مياد, رشيد (University of Eloued جامعة الوادي, 2023)
يعد إقليم التيطري من اهم الأقاليم في الجزائر، إذ تعد عاصمته المدية من اهم المدن التاريخية والأثرية العريقة التي رسمت معالمها منذ العصور القديمة، حيث تعاقبت عليها الكثير من الأمم والحضارات كالرومان، والعرب المسلمين والأتراك العثمانيين الذين جعلوا منها عاصمة لبايلك الوسط (التيطري)، مما أعطاها مكانة مرموقة ودورا فعالا في نشاط الإيالة، وذلك لقربها من دار السلطان من جهة، وموقعوها الوسطي بين بأيلك الشرق وبأيلك الغرب من جهة ثانية، وكونها تمثل جسرا يربط مناطق الشمال الجزائري بجنوبه من جهة أخرى. من خلال هذه المساهمة العلمية سوف نحاول تسليط الضوء على هذا الإقليم من حيث الموقع والمميزات الجغرافية، مبرزين في نفس الوقت أصل تسمية الإقليم ومختلف المراحل التاريخية التي مر بها. The Titeri region is one of the most important regions in Algeria, as its capital, Medea, is one of the most important historical and ancient cities whose landmarks have been drawn since ancient times, as many nations and civilizations succeeded it, such as the Romans, the Muslim Arabs and the Ottoman Turks, who made it the capital of the central Beylik (Titeri), Which gave it a prominent position and an effective role in the activity of the regency, due to its proximity to the Sultan’s House on the one hand, and its central location between the eastern baylek and the western baylek on the other hand, and the fact that it represents a bridge linking the regions of the north of Algeria to its south on the other hand. Through this scientific contribution, we will try to shed light on this region in terms of its location and geographical features, Highlighting at the same time the origin of the name of the region and the various historical stages it passed through.
مقال